2018
DOI: 10.1021/acs.iecr.8b03360
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Fault Diagnosis in Distillation Column Using Multikernel Support Vector Machine

Abstract: Fault detection and diagnosis (FDD) in process industries is an important task for efficient process monitoring and plant safety. It is also essential for improving product quality and reducing production cost by reducing process downtime. Real-time multiscale classification of faults plays a vital role in process monitoring. However, some major issues such as high correlation, complexity, and nonlinearity of data are yet to be addressed. In this paper, a fault diagnosis approach based on multikernel support v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 54 publications
0
33
0
Order By: Relevance
“…flow, top and bottom compositions, column pressure, and top and bottom level controllers. The detailed description of the development of steady-state and dynamic simulation can be obtained from our previous publications [4,5,7,25,38]. The Aspen Plus dynamic simulation is shown in Figure 1.…”
Section: Methodology 21 Aspen Plus® Steady-state and Dynamic Simulationmentioning
confidence: 99%
See 3 more Smart Citations
“…flow, top and bottom compositions, column pressure, and top and bottom level controllers. The detailed description of the development of steady-state and dynamic simulation can be obtained from our previous publications [4,5,7,25,38]. The Aspen Plus dynamic simulation is shown in Figure 1.…”
Section: Methodology 21 Aspen Plus® Steady-state and Dynamic Simulationmentioning
confidence: 99%
“…Distillation column is a multivariable system and holds a substantial part of the refinery and other chemical process industries [5,6]. The change in reboiler steam pressure, tray efficiency, feed composition, or overall pressure and temperature of distillation column may significantly affect the overall performance of the column [7,8]. It is reported that significant financial losses are incurred when a highthroughput plant is shut down or partially operated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A robust fault detection method for the distillation column was effectively verified by setting and analyzing the fault types in dynamic simulation [11]. Dynamic simulation provided a data set, at normal and faulty states, for the fault classification of multikernel support vector machines [12]. A quantitative HAZOP method with dynamic simulation as a deviation reasoning tool was developed to reduce uncertainty in manual HAZOP analysis [13].…”
Section: Introductionmentioning
confidence: 99%